Effects of Tele-Exercise and Nutrition Tele-Counselling on Fitness Level of Obese Employee during COVID-19 Pandemic Time - Mury Kuswari; Rimbawan Rimbawan; Hardinsyah Hardinsyah; Mira Dewi; Nazhif Gifari (JUARA : Jurnal Olahraga, 2022)
The unhealthy Lifestyle of office employees may affect cardiovascular disease risk and other chronic illnesses. In this ongoing COVID-19 pandemic, there’s a decrease in physical activity and exercise intensity in-office employees, while increasing psychological stress may reduce physical fitness. One of the solutions to these problems is by implementing tele-counseling and tele-exercise technology. The purpose of this study is to test the effects of tele-exercise and tele-counseling intervention against obese employees’ fitness levels. This study uses a pre-post-test quasi-experimental design on one group without a control group, with subjects consisting of males and females with BMI 25-30 kg/m2. Subjects received tele-exercise intervention for 30 minutes per session, three sessions per week for 12 weeks, while tele-counseling was done by Zoom and WhatsApp every day. Fitness tests include 1-minute push-up and sit-up count, sit-and-reach, and bleep test. Subjects experience significant improvement on all aspects of fitness level (strength, flexibility, and cardiorespiratory fitness), with the most significant improvement being flexibility. This study proves that tele-exercise and nutrition tele-counseling is an effective program to improve obese employees’ wellness. Moreover, this method is a good alternative for substituting direct, face-to-face exercise and nutrition counseling in this pandemic time.